Industrial Engineering - Akmar Mokhtar, Ainul; Muhammad, Masdi (IntechOpen, 2019)
Businesses across the world are aiming for increased productivity and greater efficiency. This can be achieved through the knowledge of industrial engineering, which is a systematic approach to streamlining the business process. This book presents the current state of the art of industrial engineering and provides useful information to those who wish to optimize their business practices while increasing customer service and quality.